2017
DOI: 10.1177/1753425917733033
|View full text |Cite
|
Sign up to set email alerts
|

Copper/zinc-loaded montmorillonite influences intestinal integrity, the expression of genes associated with inflammation, TLR4–MyD88 and TGF-β1 signaling pathways in weaned pigs after LPS challenge

Abstract: This study was aimed at investigating whether dietary copper/zinc-loaded montmorillonite (Cu/Zn-Mt) could alleviate Escherichia coli LPS-induced intestinal injury through pro-and anti-inflammatory signaling pathways (TLRs, NLRs and TGF-b1) in weaned piglets. Eighteen 21-d-old pigs were randomly divided into three groups (control, LPS and LPS + Cu/Zn-Mt). After 21 d of feeding, pigs in the LPS group and LPS + Cu/Zn-Mt group received i.p. administration of LPS, whereas pigs in the control group received saline. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In general, regardless of its subcellular localization, the regulation of autophagy is mainly characterized by the promotion of survival ( 41 ). TLR4 is recognized by ligands, such as lipopolysaccharides, to produce inflammatory chemokines and proinflammatory factors that induce inflammatory responses and modulate natural immunity ( 42 ). A study by Su et al ( 43 ) showed that the inhibition of the TLR4/MyD88/NF-κB signaling pathway was effective in ameliorating CME-induced myocardial injury chiefly by reducing myocardial inflammatory injury.…”
Section: Discussionmentioning
confidence: 99%
“…In general, regardless of its subcellular localization, the regulation of autophagy is mainly characterized by the promotion of survival ( 41 ). TLR4 is recognized by ligands, such as lipopolysaccharides, to produce inflammatory chemokines and proinflammatory factors that induce inflammatory responses and modulate natural immunity ( 42 ). A study by Su et al ( 43 ) showed that the inhibition of the TLR4/MyD88/NF-κB signaling pathway was effective in ameliorating CME-induced myocardial injury chiefly by reducing myocardial inflammatory injury.…”
Section: Discussionmentioning
confidence: 99%
“…Iron Iron is crucial for main cellular functions. It is essential for proper functioning of the immune system (Jiao et al 2017). It is required to build effective immune responses against invading pathogens such as the differentiation and proliferation of T lymphocytes and production of reactive oxygen species (ROS) to kill pathogens (Beard et al 2007).…”
Section: Regulatory Role Of Copper On Tlrsmentioning
confidence: 99%